The discipline effects of fixed exchange rates: constraint versus incentive effects and the distinction between hard and soft pegs - Chiu, Eric M. P.; Walter, Stefanie (Global economic review, 2012)
There has been much interest in whether fixed exchange rates can provide a strong source of discipline over domestic monetary and fiscal policies. We argue that previous studies, however, have not paid sufficient attention to the distinction between constraint and incentive effects and that these operate quite differently for hard and soft fixes. Using annual data for 31 emerging and 32 developing countries during 1990-2003, our analysis implies that hard fixes should have much stronger discipline effects on money growth and inflation and our empirical study supports their prediction. Our theoretical analysis suggests that neither hard nor soft fixes are likely to provide strong discipline over fiscal policy and this is confirmed by our empirical analysis as well.
Gesehen am 12.08.2018